Benchmarking da pecuária de leite no estado de Mato Grosso - Olini, Lucas Maciel Gomes (2016)
Profitability in a dairy production system represents the main indicator of production capacity. Thus, the objective was to model the determinants of profitability of dairy cattle farm by means of benchmarking (reference point analysis). Were analyzed the technological profile and the zootechnical, economic and size indicators of twenty-seven milk producers (213,6 ± 193,9 liters of milk/farm /day) over a twelve-month period. The properties were located in the northern mesoregion of Mato Grosso, the state's main dairy producer. The correlation coefficients of the indicators with the profitability were determined. After identifying the indicators that presented correlation, equations were adjusted to estimate the reference indicators in four different scenarios of the rate of return on invested capital (4, 6, 8 and 10% per year). The price of milk and the expenses with concentrated or bulky feeding in relation to the gross income of milk did not affect the profitability of the cattle raising. Indicators associated with land productivity (milk production by area and number of lactating cows per area used by the herd) had a greater impact on the profitability of dairy cattle than the indicators of herd productivity. The proportion of lactating cows in relation to the herd and milk production by total cows (and not by lactating cow) were the productivity indicators of the herd with the greatest impact on profitability. Labor productivity and labor cost (hired and familiar) had a high impact on the profitability of dairy farming, indicating the need to use labor-saving technologies. Thus, the increase in the productivity of land and labor factors and of these factors associated with increased production per farm, through the use of production technologies appropriate to the local reality and of management tools, would allow to increase the economic sustainability of cattle dairy farm. It is recommended to use the benchmarks (reference indicators) estimated in the present study to guide strategic decisions by milk producers in the State of Mato Grosso.